Assessment of heavy metals and radioactivity concentrations in Iraqi truffles - A. Amin, Sahar; A. Alsabagh, Afaf; A. Abdul Majeed, Athmar; N. Ali, Ali; M. Abdul Hadi, Ehab (International Journal of Physical Research, 2020)
Concentrations of heavy metals in several species of desert truffles, collected from different Iraqi provinces, were determined. Samples were collected from Al-Anbar Salah ad-Den and AlMuthana provinces. The levels of Cd, Cr, Pb, Mn, Ni, and Zn were analyzed. As well as the level of radon in the truffle samples were also measured using the solid-state nuclear track detector (CR-39). The results reveal that the concentrations of the investigated elements in the Iraqi truffles were below the recommended levels and the ascending order of the measured toxic elements was NiË‚MnË‚Zn. The concentrations of the other elements (Cd, Cr and Pb) were below the detection limit of the measuring method. Radon activity levels in the study truffle samples were between (156.23 to 513.83) Bq.m-3 with mean value of (323.23) Bq.m-3. the results reveal that most measured radon activity were below the world recommended value given by ICRP except Ramadi sample. All the computed values of health risk index (HR) of all elements were within safe limits (HR<1), therefore, the consumption of the investigated truffles does not pose any health risks from the investigated heavy elements and from radiological point of view.Â Â